2016
DOI: 10.1016/j.juro.2016.01.100
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Release and Deposition on Urinary Catheters Placed during Urological Procedures

Abstract: # These authors contributed equally to this work. AbstractPurpose-Catheter-associated urinary tract infections (CAUTI) account for ~40% of all hospitalacquired infections worldwide, with more than one million cases diagnosed annually. Recent data from a CAUTI animal model has shown that inflammation induced by catheterization releases host fibrinogen that accumulates on the catheter. Further, Enterococcus faecalis catheter colonization was found to be dependent on EbpA, a fibrinogen binding adhesin. We sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
126
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(138 citation statements)
references
References 25 publications
11
126
0
1
Order By: Relevance
“…The deposition of other host matrix proteins, including fibronectin and elastin, on prostheses is known to promote bacterial adhesion and facilitate persistent infection (39). Here we also show that S. aureus (i) exploits Fg deposition during a mouse CAUTI model via ClfB interactions and (ii) specifically colocalizes with Fg deposited on catheters from patients with S. aureus-positive cultures, despite the patients receiving appropriate, intensive antibiotic therapy (27). This suggests that an approach that can disrupt or prevent interaction with Fg may be developed as an antibiotic-sparing therapy.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…The deposition of other host matrix proteins, including fibronectin and elastin, on prostheses is known to promote bacterial adhesion and facilitate persistent infection (39). Here we also show that S. aureus (i) exploits Fg deposition during a mouse CAUTI model via ClfB interactions and (ii) specifically colocalizes with Fg deposited on catheters from patients with S. aureus-positive cultures, despite the patients receiving appropriate, intensive antibiotic therapy (27). This suggests that an approach that can disrupt or prevent interaction with Fg may be developed as an antibiotic-sparing therapy.…”
Section: Discussionsupporting
confidence: 56%
“…We found that Fg was deposited on all patient catheters and S. aureus colocalized with deposited Fg (Fig. 5), despite receiving intensive antibiotic therapy (27) (Table S2). Together, these data indicate that Fg deposition on urinary catheters alters the UT environment, making it more suitable for MRSA adherence and persistent colonization.…”
Section: Catheterization Creates a Permissive Environment For Mrsa Urmentioning
confidence: 88%
See 3 more Smart Citations